Peter Spier's Christmas! - Spier, Peter (New York : Bantam Doubleday Dell, 1996)
Follows three young children and their parents as they make preparations for and celebrate the holiday.
"A Picture Yearling book"--T.p.
Keywords: Christmas -- Fiction; Stories without words; Christmas -- Fiction; Stories without words